Tinjauan Hukum Pendaftaran Tanah Berdasarkan Peraturan Pemerintah Nomor 24 Tahun 1997: Studi Kasus Putusan Nomor 5/PDT.G/2024/PN BYW - Sama Hulu, Berkat; Rikmadani, Rd. Yudi Anton (Advokasi Hukum & Demokrasi (AHD), 2025)
Land registration is an essential instrument in Indonesia’s land law system to ensure legal certainty and the protection of rights for landowners. This study employs a normative juridical method with a statutory and case study approach, focusing on Court Decision Number 5/PDT.G/2024/PN Banyuwangi. The findings indicate that the implementation of land registration under Government Regulation Number 24 of 1997 still faces several challenges, including weak validation of initial documents, potential overlapping claims, and limited objection mechanisms prior to the issuance of land certificates. The panel of judges in this case declared that the transfer of land rights from the original owner to the plaintiff was legally valid, while the defendant’s demand for compensation was deemed an unlawful act. This ruling emphasizes the importance of the principles of legal certainty, legal protection, and good faith in land registration. The study recommends improving document validation, enhancing transparency in the land registration system, and optimizing the implementation of the Complete Systematic Land Registration (PTSL) program to prevent similar disputes in the future.